Design, synthesis and biological evaluation of LBM-A5 derivatives as potent P-glycoprotein-mediated multidrug resistance inhibitors. Issue 10 (15th May 2016) - Wu, Yuxiang; Pan, Miaobo; Dai, Yuxuan; Liu, Baomin; Cui, Jian; Shi, Wei; Qiu, Qianqian; Huang, Wenlong; Qian, Hai
Graphical abstract: Abstract: A novel series of P-glycoprotein (P-gp)-mediated multidrug resistance (MDR) inhibitors with triazol- N -phenethyl-tetrahydroisoquinoline or triazol- N -ethyl-tetrahydroisoquinoline scaffold were designed and synthesized via click chemistry. Most of the synthesized compounds showed higher reversal activity than verapamil (VRP). Among them, the most potent compound4 showed a comparable activity with the known potent P-gp inhibitor WK-X-34 with lower cytotoxicity toward K562 cells (IC50  >100 μM). Compared with VRP, compound4 exhibited more potency in increasing drug accumulation in K562/A02 MDR cells. Moreover, compound4 could significantly reverse MDR in a dose-dependent manner and also persist longer chemo-sensitizing effect than VRP with reversibility. Further mechanism studies revealed that compound4 could remarkably increase the intracellular accumulation of Adriamycin (ADM) in K562/A02 cells as well as inhibit rhodamine-123 (Rh123) efflux from the cells. These results suggested that compound4 may represent a promising candidate for developing P-gp-mediated MDR inhibitors.